Perceptions of peer contraceptive use and its influence on contraceptive method use and choice among young women and men in Kenya: a quantitative cross-sectional study - Lisa M. Calhoun; Anastasia Mirzoyants; Sylvia Thuku; Lenka Benova; Therese Delvaux; Thomas van den Akker; Courtney McGuire; Bernard Onyango; Ilene S. Speizer (BMC, 2022)
Plain language summary In Kenya, about 15% of women age 15-19 have already had a birth and approximately one third of these women did not want to have a child at that time. Yet about 45% of sexually active women ages 15-24 report that they currently use family planning (FP). Among young people, friends and peers are an important influence on behaviors. This study focused on a representative sample from Kenya of female and male youth (ages 15-24) who ever had sex. Men and women were asked questions about use of FP, if they think their peers use FP and about characteristics such as age and education. The results showed that young women and men who believed their peers use FP were more likely to use FP themselves. Also, young men and women who believed that peers use FP were more likely to use condoms than not use any FP and more likely to use condoms than to use another modern method of FP. Young women who thought their peers use were more likely to use another modern method (not including condoms) than to be a nonuser of FP. Programs targeting young people should include information on a range of FP methods and aim to include groups of peers and encourage open discussion.